2021
DOI: 10.1172/jci.insight.145704
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a series of hair-cell MET channel blockers that protect against aminoglycoside-induced ototoxicity

Abstract: To identify small molecules that shield mammalian sensory hair cells from the ototoxic side effects of aminoglycoside antibiotics, 10,240 compounds were initially screened in zebrafish larvae selecting those that protected lateral-line hair cells against neomycin and gentamicin. When the 64 hits from this screen were retested in mouse cochlear cultures, 8 protected outer hair cells (OHCs) from gentamicin in vitro without causing hair-bundle damage. These 8 hits share structural features and all block, to varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 59 publications
2
52
0
Order By: Relevance
“…After initial entry through MET channels, aminoglycosides accumulate and remain confined inside hair cells where they can exert their pathological effects. Based on this premise, studies have established that blocking the MET channel is an effective method of protecting hair cells from aminoglycoside-induced cell death [28,42]. However, in our study we found that neurotransmission-deficient hair cells are protected despite intact MET channel function as well as normal levels of neomycin accumulation and rates of neomycin entry (Figure 1, 3).…”
Section: Neurotransmission and Aminoglycoside Uptake Clearance And Pa...mentioning
confidence: 55%
“…After initial entry through MET channels, aminoglycosides accumulate and remain confined inside hair cells where they can exert their pathological effects. Based on this premise, studies have established that blocking the MET channel is an effective method of protecting hair cells from aminoglycoside-induced cell death [28,42]. However, in our study we found that neurotransmission-deficient hair cells are protected despite intact MET channel function as well as normal levels of neomycin accumulation and rates of neomycin entry (Figure 1, 3).…”
Section: Neurotransmission and Aminoglycoside Uptake Clearance And Pa...mentioning
confidence: 55%
“…Our data provide conclusive evidence that megalin is a critical component of AG transport into endolymph and AGs are targeted to HCs through MET channel entry. We and others have shown that AG ototoxicity can be effectively reduced by preventing AG uptake into the HCs ( 34 36 , 63 ). Multiple sites of action of AGs can be targets for ototoxicity, and many of them overlap with antimicrobial targeting, making it difficult to eliminate ototoxicity without altering antimicrobial activity ( 17 ).…”
Section: Discussionmentioning
confidence: 96%
“…Possible therapeutic targets for preventing AG ototoxicity also have been explored by blocking one of the AG transport pathways or intracellular mechanisms ( 32 , 33 ). For example, MET channel blockers ( 34 36 ) as well as antioxidants and anti-apoptotic agents were proposed with some limited efficacy ( 37 39 ).…”
mentioning
confidence: 99%
“…Auditory hair cells lacking TMC1 or carrying TMC1 deafness-causing mutations degenerate and die leading to hair cell loss, but the molecular mechanisms leading to hair cell degeneration and deafness are unknown. While wild type hair cells might use PS externalization and subsequent membrane blebbing and TMC1 removal to restore malfunctioning MET or prevent aminoglycoside overload and cell death (Kenyon et al, 2021), we propose that constitutive PS externalization in TMC1 M412K, D569N and D528N mutant hair cells may be the underlying mechanism leading to progressive hair cell loss, and ultimately, deafness in these mice and humans carrying the equivalent mutations (M418K and D572N). In fact, reduced TMC1 protein levels and immature-like bundles have been described in TMC1 D569N mice and hair cell loss can be observed in mice homozygous for any of these mutations as early as P15 (Beurg et al, 2019, Beurg et al, 2021, Marcotti et al, 2006).…”
Section: Discussionmentioning
confidence: 97%